ANALISIS BIAYA-VOLUME-LABA (COST-VOLUME-PROFIT) MULTIPRODUK SEBAGAI ALAT PERENCANAAN LABA PADA PT MARINAL INDOPRIMA DI SUMENEP - Putri, Devi Lestari Pramitha; Septyawati, Devia (Fakultas Ekonomi, Program Studi Akuntansi, 2018)
Cost-volume-profit analysis (CVP) is a useful tool for companies to measure a profit that will be planned by the company. In addition, by analyzing CVP companies will be easier to plan, control, and make a good decision for the company. This type of research is descriptive quantitative. The data type is Quantitative Data. The data source is Primary Data and Secondary Data. The data collection technique is by interview and documentation. PT. Marinal Indoprima in planning profits for 2016 using the Cost-volume-profit analysis method must sell cherry products for 3,026,713 units at a selling price of Rp 165,524 and for seaweed products at 9,419 units at a selling price of Rp 145,52. Break even point for products of the type of cherry 734,943 units with a nominal value of Rp. 123,742,868,862 and for seaweed type products is 4,773 units with a nominal value of Rp. 698,779,242. Margin Of Safety Cherimen products are Rp. 25,458,992,002, and for seaweed products Rp. 144,434,848. The level of PT Marinal Indoprima's Operating Laverage for 5.86 cherries and 60.83 seaweed products, which means that every 1% increase in sales revenue will increase the company's profit. Based on the calculation of Shut Down Point, processing of cherry and seaweed products must be stopped if the sale is at the point of closing the business of Rp. 103,893,615,707 (cherimen products) and Rp. 586,664,790 (seaweed products).